ANALISIS DAN PERANCANGAN DINDING PENAHAN RADIASI PADA RUANGAN RADIOGRAFI UMUM DI RSUD GAMBIRAN KEDIRI - Akbar Firdaus; Syahrul Romadhon; Sumaidi (LPPM Universitas Abdurrab, 2026)
The advancement of medical technology demands high safety standards, particularly regarding the use of ionizing radiation in healthcare facilities. This study aims to analyze and design radiation shielding walls for the general radiography room at RSUD Gambiran Kediri to ensure the safety of workers and the community in accordance with national standards. The research method involved evaluating radiation protection parameters, including weekly workload, occupancy factors, and the distance from the radiation source to measurement points, based on NCRP Report No. 147 recommendations and BAPETEN regulations. Analysis results indicate that the wall design, utilizing 15 cm thick lightweight concrete bricks with a 2 mm lead (Pb) lining, exceeds the minimum technical requirements of 107.2 mm brick thickness and 0.28 mm lead lining. Consequently, this design provides a sufficient safety margin and is declared safe to support diagnostic radiography service operations